(untitled) (Marketing Journal, 2025)
This article examines the methodology for assessing factors influencing the development of small business entities, the identification of factors affecting the development of small business using PEST analysis (political, economic, socio - demographic, techn ological factors), the essence of PEST analysis — determining and evaluating the impact of macro -environmental factors on the current and future performance of small business entities.